Upward gaze direction increases center of pressure displacement and decreases squat stability - Kohn, M. A.; Smith, M. C.; Goble, D. J. (International Journal of Sports Science & Coaching, 2022)
The purpose of this study was to quantify differences in barbell back squat stability as a function of gaze direction. Sixteen female subjects who were experienced in barbell back squatting performed six sets of three squat repetitions, randomized according to three gaze directions (DOWN, STRAIGHT, and UP). Stability was determined based on the displacement of center of pressure (COP) during each squat repetition, measured using a low-cost, portable force plate. Multiple t-tests with statistical significance set at p<0.05 were conducted between gaze directions and revealed significant differences in stability between the DOWN versus UP conditions. Specifically, DOWN had the smallest COP displacement, with significantly larger COP displacement in the UP condition (p=0.02). There were no significant differences when DOWN or UP was compared to STRAIGHT (p=0.22 and p=0.28 respectively). From a practical standpoint, these results suggest that having a downward gaze direction during barbell back squat will maximize stability and reduce the likelihood of injury.